Exosome-Mediated Delivery of the Neuroprotective Peptide PACAP38 Promotes Retinal Ganglion Cell Survival and Axon Regeneration in Rats With Traumatic Optic Neuropathy - Wang, Tian; Li, Yiming; Guo, Miao; Dong, Xue; Liao, Mengyu; Du, Mei; Wang, Xiaohong; Yin, Haifang; Yan, Hua (Frontiers in Cell and Developmental Biology, 2021)
Traumatic optic neuropathy (TON) refers to optic nerve damage caused by trauma, leading to partial or complete loss of vision. The primary treatment options, such as hormonal therapy and surgery, have limited efficacy. Pituitary adenylate cyclase-activating polypeptide 38 (PACAP38), a functional endogenous neuroprotective peptide, has emerged as a promising therapeutic agent. In this study, we used rat retinal ganglion cell (RGC) exosomes as nanosized vesicles for the delivery of PACAP38 loaded via the exosomal anchor peptide CP05 (EXOPACAP38). EXOPACAP38 showed greater uptake efficiency in vitro and in vivo than PACAP38. The results showed that EXOPACAP38 significantly enhanced the RGC survival rate and retinal nerve fiber layer thickness in a rat TON model. Moreover, EXOPACAP38 significantly promoted axon regeneration and optic nerve function after injury. These findings indicate that EXOPACAP38 can be used as a treatment option and may have therapeutic implications for patients with TON.